(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This article introduces the Ombudsmus Council as a proposed Fourth Branch of GovernmentQuarta Politicadesigned to protect citizens from government failures and strengthen democratic accountability. Expanding on the traditional ombudsman model, the Council would be constitutionally independent from the legislative, executive, and judicial branches, with the authority to investigate, rule on, and enforce remedies against abuses of power and policy failures. While existing democratic systems rely on checks and balances among the three traditional branches, they often lack a formal, independent institution dedicated specifically to defending citizens when those branches fall short. Unlike the mediawhich faces growing political and economic pressuresthe Ombudsmus Council would be structurally embedded in the constitution as a permanent watchdog with public oversight functions. Its tasks would include monitoring state conduct, launching inquiries, issuing binding decisions, and promoting civic education on democratic participation. This proposal is original in its call for a constitutionally mandated citizen defense mechanism, advancing current debates on democratic renewal, accountability, and institutional innovation. It builds upon and moves beyond global experiments in ombuds-type offices by formalizing their role within the constitutional architecture. Potential challenges include resistance from entrenched powers, legal questions about separation of powers, and the need for broad political consensus. Nonetheless, the model is adaptable across varied political contextsespecially where democratic backsliding or institutional distrust is prevalentoffering a replicable framework for enhancing participatory democracy and state responsiveness worldwide.